2024
DOI: 10.1021/acsami.3c15746
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Li Deposition through the Graphene-Based Ion-Flux Regulator for High-Rate Li Metal Batteries

Subi Yang,
Junghwan Kim,
Seungho Lee
et al.

Abstract: Lithium (Li) metal is considered an ultimate anode owing to its high specific capacity and energy density. However, uncontrolled Li dendrite growth and low Coulombic efficiency have limited the application of Li metal. Among various strategies introduced to address these limitations, the surface modification of polyolefin separators with functional materials has been widely adopted for improving the mechanical and thermal stabilities of polymer separators and to protect the separator from the penetration of Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…As Li metal is the lightest member of the alkali metal group and has the lowest reduction voltage (−3.04 V vs. standard hydrogen electrode), extensive research has been reported on highly promising next-generation anode materials [10][11][12]. However, the use of Li metal in liquid electrolytes faces many challenges owing to its high reactivity to nonuniform Li dendrite formation, which results in hazardous safety concerns (e.g., fire and explosion).…”
Section: Introductionmentioning
confidence: 99%
“…As Li metal is the lightest member of the alkali metal group and has the lowest reduction voltage (−3.04 V vs. standard hydrogen electrode), extensive research has been reported on highly promising next-generation anode materials [10][11][12]. However, the use of Li metal in liquid electrolytes faces many challenges owing to its high reactivity to nonuniform Li dendrite formation, which results in hazardous safety concerns (e.g., fire and explosion).…”
Section: Introductionmentioning
confidence: 99%
“…Lithium metal batteries (LMBs) using Li metals as anodes have attracted increasing attention in these years, as lithium metal has a quite high theoretical specific capacity of 3860 mAh/g and a pretty low redox potential. However, the uncontrolled dendrite growth during charge/discharge cycles caused by uneven deposition on the Li anode, along with the side reactions between liquid electrolyte and Li anode, seriously hinder the wide practical application of lithium anodes. This is because uncontrolled dendrite growth may pierce the separator and cause internal short circuits, leading to a catastrophic safety risk; the parasitic reactions will continuously deplete the electrolyte, reduce the Coulombic efficiency, and shorten the lifetime. ,,, Therefore, solving the above problems is the key to promoting the practical applications of LMBs.…”
Section: Introductionmentioning
confidence: 99%